2013
DOI: 10.1136/bmjqs-2012-001418
|View full text |Cite
|
Sign up to set email alerts
|

Identifying attributes required by Foundation Year 1 doctors in multidisciplinary teams: a tool for performance evaluation

Abstract: This study demonstrates the potential of repertory grid methodology in eliciting attributes that are important for effective teamworking, and using these to evaluate MDT working by FY1 doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Where there are data, by purely adding up the number of studies we might think that graduates are prepared for communication with colleagues and patients 2736 37 39 41 42 Although there are few studies of preparedness for multidisciplinary team-working, the evidence is relatively robust and indicates unpreparedness of graduates: thus, two of the three manuscripts suggesting problems in this area had multidisciplinary team-working as the sole focus of their work 6061 Both concluded that medical graduates have preparedness problems.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Where there are data, by purely adding up the number of studies we might think that graduates are prepared for communication with colleagues and patients 2736 37 39 41 42 Although there are few studies of preparedness for multidisciplinary team-working, the evidence is relatively robust and indicates unpreparedness of graduates: thus, two of the three manuscripts suggesting problems in this area had multidisciplinary team-working as the sole focus of their work 6061 Both concluded that medical graduates have preparedness problems.…”
Section: Resultsmentioning
confidence: 99%
“…As with earlier sections, the evidence is complex. Medical graduates often have problems with time management,27 36 37 60 68 but seem to understand their own limitations36 37 41 42 with inconclusive data on graduates' abilities to identify and organise their learning needs and reflective practice 3741 42 For this latter aspect, perhaps graduates from older curricula are less well prepared than those learning in a more contemporary way 37.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations